A new high elevation species of Oreophryne Boettger (Anura: Microhylidae) from Sulawesi, Indonesia - Putri, Auni Ade; Trilaksono, Wahyu; Kurniati, Hellen; Hitch, Alan Thomas; Jr, Andrew Engilis; Widayati, Kanthi Arum; Farajallah, Achmad; Hamidy, Amir (Zootaxa, 2023)
We examined the morphology of 50 specimens of Sulawesian Oreophryne and recognize a distinct, undescribed species. Based on morphological data and supported with phylogenetic analysis of the 16S rRNA gene, it is herein described and named as Oreophryne riyantoi sp. nov. The new species is diagnosed by having a combination of rounded snout in dorsal and lateral view, indistinct tympanum, narrow interorbital distance, small hands, small terminal discs on fingers and toes, toes without webbing, short legs, and dorsal surfaces of head, body and limbs irregularly tuberculated in life. It was found in leaf litter on the forest floor in extremely wet primary montane forest on Mount Mekongga at an altitude of 2528 m asl. The forest-dwelling habit of this terrestrial frog is unusual because other terrestrial Oreophryne occuring at high-altitude live in open grassy or fern dominated meadows. Four endemic species of Oreophryne are now known from Sulawesi. However, herpetological research activities, including high elevation surveys and additional taxonomic work, are necessary to achieve a comprehensive understanding of Oreophryne diversity and phylogeography in Sulawesi.